EBV-associated high-grade transformation of mantle cell lymphoma: A case report - Nana Matsumoto; Zenggang Pan (Elsevier, 2021)
The relationship of Epstein-Barr virus (EBV) has been well characterized with a wide range of lymphoproliferative lesions and lymphomas of B-cell, T-cell, and NK-cell origin. However, the association of EBV with mantle cell lymphoma (MCL) is exceedingly rare and not well established. We report a case of classic MCL which transformed to pleomorphic MCL after a clinical course of 19 years. Particularly, EBV infection was detected in the transformed high-grade pleomorphic MCL. Molecular and genetic analyses confirmed the clonal relationship between the original and transformed lymphomas. To the best of our knowledge, there has only been one case reported in 2003 which documented an EBV-associated high-grade transformation of MCL. Therefore, our case report further expanded the spectrum of EBV in the pathogenesis of B-cell lymphoma transformation.